THE INFLUENCE OF EFFECTIVENESS, SECURITY AND LIFESTYLE ON STUDENT INTEREST IN TRANSACTIONS USING THE QUICK RESPONSE CODE INDONESIAN STANDARD (QRIS) - Nazila Nur Aprilia; Fityan Izza Noor Abidin (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study examines the influence of effectiveness, security, and lifestyle on students’ interest in using the Quick Response Code Indonesian Standard (QRIS) for transactions. Method: A quantitative approach was applied with a sample of 187 accounting students from the 2020–2021 cohort at Muhammadiyah University of Sidoarjo. The purposive sampling technique was used, and data were collected through questionnaires based on a Likert scale derived from variable indicators. Data analysis was conducted using SPSS version 23. Results: The findings indicate that both effectiveness and security have a positive and significant impact on students’ interest in using QRIS. However, lifestyle does not have a significant effect on transaction interest. Conclusion: The results suggest that students’ adoption of QRIS is primarily driven by perceived efficiency and security rather than lifestyle factors, highlighting the importance of improving system reliability and performance to increase user engagement.